Membrane distillation : module design and modeling - Yang, Xing (2012)
Membrane distillation (MD) is an emerging technology for seawater desalination that is traditionally accomplished by conventional separation processes such as thermal distillation or reverse osmosis. It is potentially cost effective as it is feasible to utilize low-grade waste heat and/or alternative renewable energy sources. However, the industrialization of MD is impeded by several technical challenges which include the membrane pore-wetting problem, low permeability, and concentration/temperature polarization effect, etc. This thesis provides a comprehensive review on the state-of-the-art of MD technology with focuses on some areas that need to be further investigated or strengthened, such as novel membranes and improved membrane module design with the aid of mathematical modeling, which may offer strategies to address the challenges.A preliminary study of the performance improvement of the hollow fiber-based direct contact membrane distillation (DCMD) system has been conducted. The original hydrophobic polyvinylidene fluoride (PVDF) hollow fiber and two modified membranes (unmodified, plasma modified and chemically modified) were used and compared. It was found that modified membranes presented better hydrophobicity while maintaining similar structural properties and less vulnerability to pore wetting, thus resulting in more sustainable long-term performance. Single fiber tests in combination with heat transfer analysis showed that a critical length Lc existed to assure sufficient driving force along the fiber to maintain a high MD efficiency. In addition, the over MD coefficient decreased with increasing packing density.